Technological retrogression : a Schumpeterian interpretation of modernization in reverse - Endresen, Sylvi B. (Anthem other canon economics., 2021)
The aim of this book is to broaden our understanding of technological change by adopting the concept of technological retrogression. With reference to concrete cases of technological retrogression a new conceptual framework is developed. The book's exposition aims at contrasting retrogressive economic dynamics of technological change to progressive dynamics as developed by Schumpeter.